A critical view to restoring family legal ties in the Council Drective 2003/86/EC and in the Spanish Immigration Llaw - Vargas Gómez-Urrutia, Marina (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
One of the fundamental issues to implement legal measures concerning family reunification in the European Member States is to protect the family unit and respect family life, safeguarded by many instruments of international law. Administratively, in accordance with the integration policies of Member States, two mechanisms can be applied to restrict the potential access of a family member to the new territory. One, through stand still and status quo clauses (typical matters concerning migration law). Two, in international family law, interactions with the complexities of private international law (PIL) are unavoidable, which can be decisive on entry and exiting decisions concerning family regrouping. This paper provides a critical evaluation of both matters in light of the Council Directive 2003/86/CE and the Spanish regulation for family reunification.